Application of exterior calculus to waveguides - Ferraro, Rafael (2010)
Exterior calculus is a powerful tool for finding solutions to the electromagnetic field equations. Its strength can be better appreciated when applied to nontrivial configurations. We show how to exploit this tool to obtain the TM and TE modes in hollow cylindrical waveguides. The use of exterior calculus and Lorentz boosts leads straightforwardly to the solutions and their respective power transmitted along the waveguide